Comparative study between skin suture versus skin stapler in abdominal surgery - Ram Singh, Hare; Chowdary, C. Raghuram; Reddy , M. Rajavardhan (International Surgery Journal, 2023)
Background: Through the age’s man sought for methods of binding wounds to promote healing. In olden days various things were used by surgeons but the secret to achieve a good wound healing lies in meticulous tissue dissection followed by selection of suture material, methods of wound closure and postoperative complications. Staplers were originally developed to address the perceived problem of patency i.e., security against leaks of blood or bowel contents in anastomosis in particular but now. It is widely accepted that both sutures and staples can achieve the basic goals of skin wound closure. Methods: Patients admitted under various surgical units from December 2020 to June 2022 at Mamata Medical College and Hospital, Khammam. A study was carried out with 50 patients undergoing laparotomy electively and emergency. Results: Skin approximation was much faster with staple as compared to sutures. Post-operative SSI was more common with skin suture group as compared with staples. Cosmetic appearance of the scar was found to be superior in staple group in comparison to conventional suturing group. Conclusions: The results of the study indicate that skin closure by stapler can be preferred over conventional skin suture.